Adjective Clauses in Hosseini’s The Kite Runner: A Systemic Functional Analysis in Translation Studies - Ahmad Yusuf Firdaus; Yopi Thahara (Unipdu Jombang, 2022)
This research analyzed translation techniques used to translate adjective clauses found in the novel The Kite Runner, described the shifts of semantic categories in some of the translated clauses, and described the effects of the techniques used on the quality of the translated clauses. This study falls into the class of descriptive qualitative research. The main source of the data is the novel The Kite Runner, written by Khaled Hosseini and its Indonesian version. The secondary source of the data is the information given by raters and respondents through questionnaires given to them. The result of this study shows that eleven translation techniques are used to translate 268 data analyzed in this research. In terms of semantic category, 55 data are believed to experience shifts in semantic categories. In general, 231 (86,1%) data are accurate, 35 (13%) data are less accurate, and 2 (0,74) data are inaccurate. In terms of the acceptability, 234 (87,3%) data are acceptable, 31(11,5%) data are less acceptable, and 3 (1,1%)data are unacceptable. Meanwhile, viewed from the level of readability, 226 (84,3%) data are highly readable, 40(14,9%) data moderately readable, and 2 (0,74%) data hardly readable.